Pengaruh Pemberian PGPR (Plant Growth Promoting Rhizobacteria) dan Dosisnya terhadap Perkembangan Penyakit Layu Bakteri pada Tanaman Tomat - Muhammad Bahry Syawal Syahputra; Achmad Himawan; Elisabeth Nanik Kristalisasi (AGROISTA : Jurnal Agroteknologi, 2026)
Ralstonia solanacearum is a disease-causing bacterium in tomato plants that can decrease yield quantity and quality.  This soil-borne disease can cause massive economic losses, with crop yield losses ranging from 30% to 100% (total failure) due to plant death before production. Conventional disease control generally relies on chemical pesticides, which can damage and pollute the environment. Therefore, an alternative approach is needed to reduce their use, specifically through the application of PGPR (Plant Growth-Promoting Rhizobacteria). One type of PGPR bacteria that can act as antagonists is Bacillus sp. and Pseudomonas. This study was conducted to determine the ability of Bacillus sp. and Pseudomonas to inhibit Ralstonia solanacearum, which causes bacterial wilt disease in tomato plants. The method used in this study is Completely Randomized Design with separate control (RAL+1) consisting of 2 factors. The first factor is PGPR, PGPR 1 and PGPR 2. The second factor is the PGPR dosage which is 10, 20 and 30 ml/plant.  Thus, 2 × 3 = 6 combinations were obtained. Each combination and the control was replicated five times, so the total number of plants in this study was 35. The data were analyzed using a contrast test and ANOVA (analysis of variance) at the 5% significance level and Duncan's Multiple Range Test (DMRT) at the 5% significance level. The research results show the incubation period in the control treatment was 5 days after planting to show symptoms of wilt disease. The PGPR treatment at 10 ml per plant showed symptoms after 13 days for both types of PGPR. The PGPR doses of 20 ml per plant and 30 ml per plant did not show wilt disease symptoms. In the control treatment, all plants were infected with Ralstonia solanacearum. The PGPR 1 treatment at 10 ml/plant resulted in 60% infection, while the PGPR 2 treatment at the same dose resulted in 40% infection. No infection was observed at doses of 20 and 30 ml/plant